Interactive effects of altered rainfall and simulated nitrogen deposition on seedling establishment in a global biodiversity hotspot - Standish, R.; Fontaine, J.; Harris, Richard; Stock, W.; Hobbs, R. (Wiley-Blackwell Publishing, Inc., 2012)
Understanding the interactive effects of global change drivers on vegetation is critical for ecosystem management and restoration, particularly in the Mediterranean-climate biodiversity hotspots of the world. Climate change, habitat loss and nitrogen deposition have been identified as the key threats to biodiversity loss in these regions, yet their combined effects are poorly understood. We measured the interactive effects of rainfall manipulation (reduction, control, addition) and nitrogen deposition (N addition, N + P addition, and unfertilised) on the establishment of 19 Banksia-woodland species planted at three sites in southwestern Australia. Seedling survival and aboveground biomass was increased with water addition but was not affected by rainfall reduction. N addition alone did not impact seedling survival and growth, but interacted with rainfall manipulation and site in unpredictable ways. Treatment effects were context dependent, which we attributed to historic nutrient enrichment and competitive exotic species that prevented seedling establishment. Plant species (n = 6) varied greatly in their water-use efficiency and nitrogen-use efficiency responses to the imposed treatments, which underscores the difficulty of generalising results to larger numbers of species. Despite our finding that rainfall manipulation and nutrient addition have complex, and in some cases antagonistic effects on seedling survival and growth in Banksia woodlands, our results suggest that local context (i.e. invasive species, land-use history) will have as much influence on seedling establishment as global changes in climate and nitrogen deposition.We call for more field experiments and predictive models to explore further the importance of ecological context in determining the interactive effects of multiple global change drivers on ecosystems. Finally, to realize effective biodiversity conservation, local management interventions that address invasive species and associated habitat degradation will be as critical in the future as they are now.